2011
DOI: 10.1007/s00216-010-4629-0
|View full text |Cite
|
Sign up to set email alerts
|

An integrated method for degradation products detection and characterization using hybrid ion trap/time-of-flight mass spectrometry and data processing techniques: Application to study of the degradation products of danofloxacin under stressed conditions

Abstract: A new strategy using hybrid ion trap/time-of-flight mass spectrometry coupled with high-performance liquid chromatography and post-acquisition data mining techniques was developed and applied to the detection and characterization of degradation products of danofloxacin. The degradation products formed under different forced conditions were separated using an ODS-C18 column with gradient elution. Accurate full-scan MS data were acquired in the first run and processed with the combination of extracted ion chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…The products from MARSturini et al, 2010;Sturini et al, 2012b), CIP(Mella et al, 2001;Sturini et al, 2012b), DAN(Ge et al, 2010;Liu et al, 2011;Sturini et al, 2012b), LEV(Albini and Monti, 2003;Sturini et al, 2012b), except for the minor products proposed to arise through demethylation, L7 (compareGe et al, 2010) and piperazine the ring cleavage, L6 (compare De Witte et al, 2009), have been here confirmed. Molecular structures are reported in Supplementary, figures from S2 to S5.…”
supporting
confidence: 63%
“…The products from MARSturini et al, 2010;Sturini et al, 2012b), CIP(Mella et al, 2001;Sturini et al, 2012b), DAN(Ge et al, 2010;Liu et al, 2011;Sturini et al, 2012b), LEV(Albini and Monti, 2003;Sturini et al, 2012b), except for the minor products proposed to arise through demethylation, L7 (compareGe et al, 2010) and piperazine the ring cleavage, L6 (compare De Witte et al, 2009), have been here confirmed. Molecular structures are reported in Supplementary, figures from S2 to S5.…”
supporting
confidence: 63%
“…Under these conditions, five photodegradation products of DAN were identified. [33] Liu et al [34] performed a stability study of DAN under stressed conditions. The photostability testing was carried out by exposing the solution of drug in water to UV fluorescent light (208 Wh=m 2 ) at room temperature for 12 h. For the characterization of DAN and its degradation products, hybrid ion trap=time-of-flight (IT=TOF) mass spectrometry coupled with a HPLC system was used.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32] Analysis of DAN photodegradation in solutions was investigated in several papers. [12,13,33,34] Sturini et al [12] performed forced photodegradation studies of DAN in raw river water using sunlight as the light source. Irradiation was undertaken outdoor in July, at temperatures ranging from 27 C to 30 C. The photodecomposition of DAN was monitored by HPLC-FD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HPLC-UV and HPLC-PAD are two largely used stability-indicating methods, but Liquid Chromatography Coupled to Mass Spectrometry (LC-MS) has become the gold standard technique in drug degradation monitoring due to its high DP sensitivity and selectivity as a result of the detailed structural information it provides (Zhang and Pramanik, 2010;Jocic et al, 2009;Bhardwaj, Singh, 2008;Liu et al, 2011b;Pan et al, 2011). At present, direct MS analysis approaches using soft ionization methods applied to drug pills have been reported and may also be suitable for some drugs (Amaral et al, 2011).…”
Section: Introductionmentioning
confidence: 99%